Axial Concentration Profiles and NO Flue Gas in a Pilot-Scale Bubbling Fluidized Bed Coal Combustor - Tarelho, Luís António da Cruz (2012)
Atmospheric bubbling fluidized bed coal combustion of a bituminous coal and anthracite with particle diameters in the range 500-4000 ím was investigated in a pilot-plant facility. The experiments were conducted at steady-state conditions using three excess air levels (10, 25, and 50%) and bed temperatures in the 750-900 °C range. Combustion air was staged, with primary air accounting for 100, 80, and 60% of total combustion air. For both types of coal, high NO concentrations were found inside the bed. In general, the NO concentration decreased monotonically along the freeboard and toward the exit flue; however, during combustion with high air staging and low to moderate excess air, a significant additional NO formation occurred near the secondary air injection point. The results show that the bed temperature increase does not affect the NO flue gas concentration significantly. There is a positive correlation between excess air and the NO flue gas concentration. The air staging operation is very effective in lowering the NO flue gas, but there is a limit for the first stage stoichiometry below which the NO flue gas starts rising again. This effect could be related with the coal rank.